Increasing Tension and Japan: East Asia in the 2010s - Murakami, Yusuke (2021)
This article analyzes the more and more tense situation in East Asia of the 2010s and Japan’s challenges in the face of this situation. More than thirty years after the fall of the Berlin Wall, the order and status quo of the second half of the last century have been strongly destabilized both globally and in various parts of the world. East Asia, where Japan is located, is the region where these global dynamics have been most acutely felt, and in recent years, together with the Middle East, has become a potential «powder keg of the world». Historically, Asia has not reached a level comparable to that of Europe in terms of the institutionalization of regional order among its component countries. The precarious post-war status quo has been profoundly shaken in this century. The inconsistent diplomatic-strategic position of the United States has allowed the expansionism of the emerging China, while South Korea, the bridgehead of the United States’ diplomatic-strategic alliance in the region of post-war, has rather moved closer to China and North Korea. In the face of ever-increasing tension, Japan nowadays more than before face the challenge of breaking the post-war «inertia» to come to define its political role in the region and the world in the search for a new regional order of the middle- and long-term.